PENGARUH PERBEDAAN LAMA WAKTU KEJUTAN PANAS TERHADAP DAYA TETAS (Hatching Rate) PADA METODE GYNOGENESIS MEIOSIS IKAN MAS (Cyprinus carpio) - Achmad Sudianto (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2018)
AbstractCarp is a freshwater fish, body shape is long and somewhat rounded with a small head, the high back and across large scaly body.The development of aquaculture carp (Cyprinus carpio) is progressing very rapidly with cultivation system are manifold. Pisciculture technology will not form without yielding seeds followed by genetic improvement effort. To improve the quality of the parent, the parent needs to be purified race carp (Cyprinus carpio) that exist so that the resulting pure strain. The success of seed carp, especially at this stage of the enlargement is determined by the quality of the seed. Breeding programs developed at this time is the method gynogenesis. Ginogenesis method is the process of female gamete without interference from male gamete gene.The experimental design used in this study is completely randomized design (CRD) is equipped with 3 treatments and 3 replications. Analysis using analysis of variance, with the distribution table F or F test that compares the value of F arithmetic with F table.Based on the analysis of research data on the influence of the length of time a different heat shock against the hatchability of eggs carp (Cyprinus carpio) method gynogenesis meiosis, based on the results of research, treatment A showed optimal results with an average 17.33, treatment B showed 12. 33 and C treatment showed 7.00. Based on calculations obtained ANOVA calculated F value (47.29)> F 1% (18.00) but larger than F 5% (6.49) then H1 is rejected at the level of a = 1% and H0 highly significant conclusions (hight significant). Key words : Heat Shock, Gynogenesis Meiosis, Hatching rate.